درجة ممارسة للإبداع الإداري لدى القادة التربويين في مديريات التربية والتعليم في محافظة إربد - عبابنة، رامي محمود إسماعيل; الشقران، رامي بن إبراهيم بن عبدالرحمن (جامعة البحرين - مركز النشر العلمي, 2013)
هدفت هذه الدراسة إلى الكشف عن درجة ممارسة الإبداع الإداري من قبل القادة التربويين في مديريات التربية والتعليم في محافظة إربد من وجهة نظرهم, تكونت عينة الدراسة من القادة التربويين في مديريات التربية والتعليم في محافظة إربد (الرمثا، إربد الأولى). للعام الدراسي 2010/ 2011، والبالغ عددهم (223) قائداً تربوياً. تم تطوير أداة للدراسة تكونت من (20) فقرة، ركزت على قياس درجة ممارسة الإبداع الإداري من قبل القادة التربويين. تم التأكد من صدق الأداة وثباتها، وقد توصلت الدراسة إلى إن درجة ممارسة الإبداع الإداري من قبل القادة التربويين في مديريات التربية والتعليم في محافظة إربد جاء بدرجة متوسطة في المجالات (تبني وتشجيع الإبداع، وتطبيق الإبداع) والأداة ككل، فيما حصل مجال "بيئة وأساليب العمل" على درجة ممارسة مرتفعة، وعدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α= 0,05) في جميع مجالات درجة ممارسة الإبداع الإداري من قبل القادة التربويين في مديريات التربية والتعليم في محافظة إربد و الأداة ككل تعزي المتغيرات (الخبرة العملية، المديرية، المسمى الوظيفي). The purpose of this study is to identify the degree of practicing administrative creativity by educational leaders in irbid educational directorates as perceived by them, the study sample consisted of educational leaders in irbid educational directorates (Ramtha directorate, first Irbid directorate), during the academic year 2010/ 2011, and numbered (n= 223). The researchers prepared & developed a questionnaire consisting of (20) items, focusing on measuring the degree of practicing administrative creativity by educational leaders, validity and reliability coefficients were ensured for the tool, the findings of the study were as follows: The degree of practicing of administrative creativity by educational leaders showed an average degree on the tool as whole, and on tow domains (adopting creativity, and applying creativity), and showed a high degree on the domain (work environment). There are no statistical significant differences at the significance level of (α=0, 05) on all domains of the degree of practicing administrative creativity by educational leaders, and on the tool as whole due to the variables (practical experience, directorate and job title).
755189 803787 706126 730460 704589 732946 666866 799995 766023 795087 677937
Keywords: الأردن -- الإدارة التربوية -- الإبداع الإداري -- القيادة الإدارية -- مديريات التربية والتعليم -- محافظة إربد -- القيادة التربوية -- الأهداف التعليمية -- التفكير الإبداعي